Konnektorer i avancerade svenskinlärares och infödda språkbrukares texter - en systemisk-funktionell analys - Vaakanainen Veijo (Föreningen för nordisk filologi, 2022)
The aim of this paper is to examine how Finnish learners of Swedish at CEFR levels B1, B2 and C1 use connectors in written narratives. The use of connectors in learner texts is compared with connector use in texts written by native speakers of Swedish. The theoretical framework of the study is systemic functional linguistics (Halliday & Matthiessen 2014). The study investigates what lexicogrammatical resources learners at different CEFR levels use in order to realize logic-semantic relations and conjunction -inside and between clauses and clause complexes.
The results show that there are no big differences in how learners at different levels of proficiency use connectors. The more advanced learners at level C1 use less frequent connectors like dessutom (furthermore) and med andra ord (in other words). Compared to the native speakers of Swedish, there are some differences: learners use almost exclusively the connector när (when) when they realize temporal enhancement whereas native speakers also use the connectors så (so) and då (then). In case of causal enhancement native speakers use the connectors för and för att (for) when L2 writers use the connector eftersom (because). The results correspond to the descriptors in the CEFR. In future research, the use of connectors could also be studied during the writing process and not only in products. Furthermore, it would be advisable to examine the use of connectors in different text types.
-